Researching oil capacity of moss fuscum peat to the commercial oil and stable gas condensate - Chukhareva N. V. Natalia Vyacheslavovna (2012, 2012)
The articles talks about influence of fractional composition of moss fuscum peat on its oil capacity. The technique for determining oil capacity of peat are discribed. The experiments were carried out for hydrocarbons with different density ( р =880 kg/m3 and р =770 kg/m3.